Avaliação do equilíbrio postural em mulheres com dor cervical - Soares, Juliana Corrêa (2012)
Neck pain has been considered a costly musculoskeletal problem, with impacts on health and quality of life of individuals may be related to repetitive strain and maintenance of postures. These changes cause mechanical and nociceptive disorders of the neck region may cause balance disorders. Maintenance of postural balance occurs through the action of the postural control system, any compromise of this system can lead to body imbalance. The dissertation was divided into two research papers, with different objectives. The first aim was to evaluate the influence of neck pain in women of postural control and verify the relation between pain and the possible changes in sensory systems and body posture and in the second, to investigate the correlation between the intensity of pain, head posture and postural sway. Neck pain group was composed of women, aged between 20 and 50, with neck pain for more than three months and the control group of women without neck pain. For characterization of the groups used interview, neck disability index (NDI) and Visual Analogue Scale. Postural balance was assessed by a force platform with acquisition frequency of 100 Hz. Postural balance with manipulation of the sensory systems was evaluated by Dynamic Posturography Foam-laser. Posture was assessed by the Postural Assessment Software in the sagittal plane right. Normality of variables was checked by Shapiro-Wilk test, and Student t test and Mann Whitney test for comparison between groups. The relationship between variables was assessed by Spearman correlation test. Significance level of 5%. Groups were homogeneous in date demographics. Variables of postural balance showed higher amplitude and velocity of displacement of the center of pressure in the neck pain group, showing greater postural sway in this group. There were significant differences in craniovertebral angle, being lower in symptomatic women, showing forward head posture. In dynamic posturography difference was observed between the groups and the score obtained by the group with neck pain in the six sensory conditions showed that postural balance showed greater impairment. Neck pain and forward head posture have a deleterious effect on postural control in symptomatic women. Pain intensity correlated with the COP sway area and the craniovertebral angle indicating that women with cervical pain had forward head posture associated with a lower postural control.